Differences in Heart Rate and Oxygen Saturation of Babies Who Have Initiated Early Breastfeeding and Not Initiated Early Breastfeeding - Ulfa Nadiya Putri Utami; Mardiana Ahmad; Ema Alasiry; Yuliana Syam; Andi Nilawati Usman; Sri Ramadhani (Sarana Ilmu Indonesia (salnesia), 2022)
Early Initiation of Breastfeeding (IMD) is one of the efforts in the delivery room that has proven to have many benefits, but its implementation is still in accordance with the existing Standard Procedures so that the expected results are not appropriate and the provision of IMD is still low. The population of this study were all babies born with normal baby weight. The sample in the study amounted to 510 infants consisting of 255 infants with the IMD group for 1 hour according to the SOP and 255 groups that did not do IMD. This research is an observational study with a prospective cohort approach. sampling technique used purposive sampling. Data using a questionnaire instrument and data analysis using Chi-Square test, Fisher Exact test and General Linear Model + Post Hoc. The study found the baby's heart rate at 15 minutes (p-value =0,028) and 30 (p-value=0,002) (p-value<0,05) and 45 minutes (p-value=0,062) and 60 minutes (p-value=0,688) (p-value>0,05) using the Chi-Square test, Fisher Exact test. While the oxygen saturation of newborns at 15, 30, 45 and 60 minutes was 0,000 (p-value<0,05) using the General Linear Model+Post Hoc test. There was a difference in the baby's heart rate between the groups who did IMD and those who didn't do IMD at the 15th and 30th minutes.